DEVELOPMENT OF A THERMAL MODEL OF A SOLAR POWERED VAPOUR ABSORPTION REFRIGERATION SUPPORTED GREENHOUSE FOR STRAWBERRY CULTIVATION. Issue 1 (February 2021) - Ghosh, Subhadeep; Ganguly, A.
Abstract: In this paper, a novel scheme of a solar powered vapour absorption refrigeration supported greenhouse with indirect evaporative cooler has been proposed. The main objective of this work is to create a favorable microclimatic condition for strawberry cultivation inside the greenhouse for a country with sub-tropical climatic conditions like India when the ambient temperature and humidity are high. The maximum yield of strawberry is achieved for a temperature ranging between 15-25 °C with a relative humidity varying from 55 to 65%. It is quite impossible to achieve a favorable temperature range for strawberry cultivation in the greenhouse under such condition by using the existing greenhouse cooling techniques. A double effect parallel flow LiBr-H2 O absorption cooling system along with an IDEC powered through solar energy has been used. A thermal model for the greenhouse has been developed and analyzed for the climatic condition of Kolkata, India. The study reveals that the proposed system can very well maintain a conducive climate for the growth of target plantation for the given location.